Macro Ergonomic Analysis and Design for Optimizing the Work Environment : A Literature Review - Suci Ayu Lestari; Nurul huda, Listiani; Ginting, Rosnani (Jurnal Sistem Teknik Industri, 2023)
The purpose of this literature is to understand the application of macroergonomics in various fields. Macroergonomics is the study of work systems which include organizational structures (complexity, formalization, centralization, policies, and processes) with a socio-technical approach used to improve work systems. The method used is a thematic analysis of articles on the application of macroergonomics in various industries. Based on the results of the article review, the process of implementing macroergonomics is analysis, design, implementation, control, and evaluation. All review articles carry out macro ergonomics analysis and design within the scope of the work system as a whole but do not intervene in all factors/problems. The reviewed articles show that the intervention is carried out only on a few factors, where human and organizational factors are always involved. The application of macroergonomics can achieve many goals at once that are beneficial to organizations, workers, and even consumers. The highest frequency of macro ergonomics objectives in consecutive review articles was: quality, occupational health, safety, work existence, productivity, efficiency, and effectiveness.